2016
DOI: 10.1016/j.enconman.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new steady state zero-dimensional simulation model for woody biomass gasification in a full scale plant

Abstract: A new steady state zero-dimensional simulation model for a full-scale woody biomass gasification plant with fixed-bed downdraft gasifier has been developed using Aspen Plus®. The model includes the technical characteristics of all the components (gasifier, cyclone, exchangers, piping, etc.) of the plant and works in accordance with its actual main control logics. Simulation results accord with those obtained during an extensive experimental activity. After the model validation, the influence of operating param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 37 publications
(47 reference statements)
2
36
0
Order By: Relevance
“…Extracting energy from biomass or organic solid waste requires biochemical and/or thermochemical processes [10]. During biochemical processes like fermentation, biomass is converted to biofuels through the digestive action of living organisms.…”
Section: Introduction and Objectivesmentioning
confidence: 99%
“…Extracting energy from biomass or organic solid waste requires biochemical and/or thermochemical processes [10]. During biochemical processes like fermentation, biomass is converted to biofuels through the digestive action of living organisms.…”
Section: Introduction and Objectivesmentioning
confidence: 99%
“…Among the various alternative energy sources, biomass has obtained more interest since it is the only suitable and renewable primary energy resource that can provide alternative transportation fuels [3] [4] [5]. Extracting energy from biomass requires biochemical or thermochemical processes [6]. During biochemical processes, biomass is converted to biogas and residual by the digestive action of living organisms.…”
Section: Introductionmentioning
confidence: 99%
“…For the other syngas components, errors were in the range of 10-30%. Such relatively high errors are anticipated when equilibrium models are implemented [50,51]. Overall, it is shown that the developed model can reliably predict the lower heating value of the produced syngas and the cold gas efficiency of the process which would subsequently be used as input for the LCA approach.…”
Section: Literature Datatitlementioning
confidence: 94%
“…The first reactor is fed with air to simulate the oxidation zone, and the second one simulates the reduction zone at a lower temperature than that of the oxidation zone. According to various literature sources, equilibrium models, implementing RGIBBS reactors, tend to overestimate CO and H 2 and underestimate CH 4 and CO 2 volume fractions [50,51]. Various solutions have been proposed.…”
Section: ∆H (Kj/mol) Reaction Number Reaction Namementioning
confidence: 99%